2012
DOI: 10.2169/internalmedicine.51.7987
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Nursing and Healthcare-Associated Pneumonia: A Japanese Variant of Healthcare-Associated Pneumonia

Abstract: Objective The aim of this study was to describe the epidemiology, clinical features, antimicrobial treatment, and outcomes of patients with nursing and healthcare-associated pneumonia (NHCAP); a new category of pneumonia proposed by the Japanese Respiratory Society. Methods We conducted a retrospective analysis of a prospectively collected database of patients with NHCAP and community-acquired pneumonia (CAP) hospitalized at a single center between January 2008 and December 2010, and compared their clinical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 18 publications
6
53
0
Order By: Relevance
“…It is thought that NHCAP is a variant of HCAP, proposed by the ATS and the IDSA in 2005, on the basis of the Japanese system of healthcare and social health insurance 2) . According to previous reports, patients with HCAP have tendency toward having poor prognoses because they were more likely to have drug-resistant pathogens and to have been initially administered inappropriate antimicrobial than the patients with pneumonia who do not meet the criteria for HCAP 3) 5) 6) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that NHCAP is a variant of HCAP, proposed by the ATS and the IDSA in 2005, on the basis of the Japanese system of healthcare and social health insurance 2) . According to previous reports, patients with HCAP have tendency toward having poor prognoses because they were more likely to have drug-resistant pathogens and to have been initially administered inappropriate antimicrobial than the patients with pneumonia who do not meet the criteria for HCAP 3) 5) 6) .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that NHCAP is a variant of healthcare-associated pneumonia (HCAP), proposed by the American Thoracic Society (ATS) and the Infectious Disease Society of America (IDSA) in 2005 1) , based on the Japanese healthcare and social health-insurance system 2) . NHCAP generally develops in patients with various complications or in bedridden elderly patients 2) . It has both the clinical characteristics of community-acquired pneumonia (CAP) and those of hospital-acquired pneumonia (HAP) 2) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishida et al reported 451 NHCAP patients with a mean age of 82 years; the mortality rate during hospitalization was 13.1%; and the percentage of patients given penicillin antimicrobial agents containing a β-lactam inhibitor was 74% in a community hospital in Japan [19]. Oshitani et al reported 477 NHCAP patients with a mean age of 84 years; the mortality rate during hospitalization was 24.7%; and the percentage of patients initially treated with ABPC/SBT was 64.6% [20].…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, the Japanese Respiratory Society proposed a modi ed concept of HCAP called nursing and healthcare-associated pneumonia , considering the epidemiological and social environmental situations in Japan 37 . Ishida et al 38 revealed the usefulness of the guidelines in a prospective manner. To de ne better strategies and to mitigate negative outcomes from HCAP, further studies are needed to identify predictive factors of MDR pathogens and prognostic factors.…”
Section: Discussionmentioning
confidence: 99%